Modification of biochar by Fe2O3 for the removal of pyridine and quinoline - Xu, Hanjiang (Environmental technology, 2018)
The biochar produced by pyrolysis at 600°C from powdered mango bark impregnated with iron, namely Fe2O3/biochar, was recognized as a multifunctional material for environmental applications. This work aims at using the above material for the removal of pyridine and quinoline from aqueous solutions. The physico-chemical properties of synthesized biochars were studied systematically with several commonly used material characterization methods including scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) and Fourier transform infrared spectrometer (FTIR). Structural and morphological analyses of the biochars showed that Fe2O3 particles were nanosized and distributed evenly on the surface of biochar, and thus exhibited great adsorption capacity for the removal of pyridine and quinoline. In addition, the results suggested that the main magnetic phase is maghemite (Fe2O3). The modified biochar showed high removal capacity (99%) for quinoline, but the removal capacity of pyridine was only 73%. The pH experiment in this passage indicated that both pyridine and quinoline reached a maximum adsorption amount at pH near 9.0. Adsorption kinetics suggested that the pseudo-second-order was well fitting the experiment data. The equilibrium study showed that the Langmuir model can adequately describe the adsorption process for pyridine and quinoline. The main mechanism of pyridine and quinoline removal was possibly electrostatic interactions and π-π interactions between the modified biochar and the adsorbate